PENGARUH VIRAL MARKETING TERHADAP PEMBELIAN ON LINE DI MEDIA SOSIAL - Anggarini, Desy Tri (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
Viral marketing is amarketing technique by using social networks (in the form of video, games, music, pictures and text)is then the productor service maybe forwarded viae-mail services, multimedia and social media. The purpose of research is to analyze the effect of providing information to the viral marketing acceptance, accessing content on viral marketing acceptance, sharing content to the viral marketing acceptance, sharing content with respect to providing information, sharing content for accessing content, risk acceptance towards providing information, risk acceptance of accesing conten, personal attachment against providing personal information, sharing content, attacment against attacment against sharing personal content.Consumers who have researched social networking such as facebook as a sample. Primary data collected through sampling techniques and with the help of a questionnaire. Analysis (SEM) with AMOS software was used to test the hypothesis.Results of testing has been done, it can be inferred that there was a positive influence in the viral marketing activity between providing information with viral marketing acceptance, accessing content with viral marketing acceptance, sharing content with viral marketing acceptance, sharing content with providing information, sharing content with accessing content, risk acceptance by providing information, risk acceptance by accesing content, personal attachment by providing information, accesing content by accesing content , personal attachment to sharing content Keyword: viral marketing, social media, the internet